Em nome da modernidade: uma educação multifacetada, uma cidade transmutada, um sujeito inventado (Montes Claros, 1889-1926) - Luciano Pereira da Silva (2012)
The transition from the 19th century to the 20th century is characterized as an era marked by great social transformations. Combined, revolutions such as the bourgeois revolution and the industrial revolution and the adoption of a new social vision resulted in the advent of modernity. This process, derived from large urban centers of Western Europe, spread across different countries. In this context, the ideals of modernization are noticed even in those areas that experienced more intensely, in other chronological milestones, the urban growth and the industrialization. Men had to be ready for a new reality by adopting lifestyles and etting up daily routines that would better fit a new world planned to be built soon. Thisdissertation has as its object of study the manifestations of modernization of the ruling elite from the most important city in northern Minas Gerais, Montes Claros (city of Montes Claros, State of Minas Gerais, southeast Brazil) between the years 1889 and 1926. Thepresent study is based on the main assumption that the discourses of modernity were disseminated in various ways and had influence on local transformation processes. Despite the fact that these discourses, originated mainly from the elites, were met with some resistance, they were still shared by part of the population. One of the reasons for thisresearch to be done arouse from the questioning of the ideals and methods used outside the institutionalized, formal school environment during that period in order to teach appropriate behaviour to the population. In order to uncover and scrutinize the problem posed, we chose to focus on the changes in the city life represented by what was published in newspapers during that time. Thus, the main source used in this study was the periodical press. As an additional source of information, publications from local memorialists were also used. Itshould be emphasized that, even under the direction of a small group which belonged to the economic and political elite of the city, the newspapers did not express a single meaning to the process of modernization of the city since the elite itself was very diverse andpolysemic. The elite itself would give several views on what was perceived and cosidered as modern, and would also express, in many instances, conservative values. In addition, the press would use the plural in order to communicate with the general population since bothliterate and illiterate individuals were, in many ways, part of the written culture. Analysis of sources allowed us to establish the following axes for the process of modernization of the society under study: (1) the role of the periodical press (perceived as a privileged teaching tool for population education); (2) the changes in the materiality of the city (e.g. streetwidening, modernization of buildings, use of electric light, etc.), (3) implementation of action plans on improved hygiene and sanitation services (especially those propagated by virtue of a supposedly backward culture of the backcountry), and (4) leisure activities (wiseuse of leisure time) [especially soccer].